Enhanced isolation with defected ground structure in MIMO antenna. Issue 24 (1st November 2014) - Anitha, R.; Sarin, V.P.; Mohanan, P.; Vasudevan, K.
Abstract : A defected ground structure (DGS) for improving isolation between four ports in a collocated multiple‐input–multiple‐output (MIMO) antenna is proposed. Isolation improvement by 7 dB is achieved by reducing surface waves within the dielectric substrate. Mutual coupling values as low as −25 dB are obtained along both the E ‐ and H ‐planes. The MIMO antenna includes a square patch antenna surrounded by a square ring patch antenna with the DGS etched in the form of a square ring. The DGS effectively suppresses the cross‐polarisation levels for all radiating modes. The design and effectiveness of the DGS in improving isolation for a fabricated 4‐port antenna are discussed.